PHILOLOGICAL APPROACH IN THE STUDY OF ISLAMIC TEXTS: A Study of the Requirements of a Philologist/Muhaqqiq - Kasriadi, Kasriadi; Harun, Hamzah; Santalia, Indo (Aqidah-Ta: Jurnal Ilmu Aqidah, 2023)
Philology is one approach that can be used in the study of religions. This is very relevant considering that the study of every religion always has something to do with sacred texts, as well as manuscripts. This research focuses on knowing the meaning of philology, the urgency of philology/tahqiq in the study of religions and Islamic studies, as well as the requirements of a philologist/muhaqqiq. This research uses a quantitative descriptive approach with a type of library research, namely research that uses data collection techniques by analyzing literature, books, documents, and various reports available digitally and in print related to the research theme. The results of the research show that philology/text study is a study in conducting a study by conducting text criticism. In this sense, Philology is known as the study of the intricacies of texts. The Urgency of the Philology/ Manuscript Study Approach is currently considered important to be studied more deeply, including the two objects of study. The first is towards the study of the study of religions, this is intended to be an additional approach in analyzing, researching a text or religious texts. Second, to the study of the study of Islamic thought. The importance of this philology in the object of Islamic study can be seen from three issues whose object of study is the Qur'an, al-Hadith and the philological approach to texts, manuscripts and books (heurmeneutics). The requirements for a Muhaqqiq are grouped into two. First, general requirements, meaning that everyone who wants to engage in philological studies must have a basis for the first requirement. While the second condition contains additional conditions as added value for a philologist/Muhaqqiq.